Geological History Reconstruction using Stratigraphic Analysis: A Case Study of Kampung Baru, West Sumatra - Putri, Helen Dwi; Setiawan, Budhi; Rochmana, Yogie Zulkurnia (Journal of Earth and Marine Technology (JEMT), 2024)
The reconstruction of geological history includes the development of rocks and volcanic deposits on a depositional pattern consisting of various types of sedimentary materials accumulated over a long time, which involves depositional changes. Depositional changes require geological comprehension in analyzing and understanding the geological processes involved in their evolution. For this reason, stratigraphic analysis is a very relevant approach to discussing rock layers, including significant environmental changes during their geologic history. The purpose of this research is to find out the geological processes that have contributed to the formation of the earth in the past. The method in this research is a stratigraphic analysis carried out from field observation data carried out directly at the outcrop. Deposition began with the re-deposition of the Pre-Tertiary (Triassic)-aged Porphyry Quartz Dasite Formation. In the Late Oligocene Epoch, the Sawahtambang Formation was deposited, which formed in the braided river characterized by the presence of sedimentary structures in the form of lamination and cross lamination. In the Early Miocene to Middle Miocene, the transgression process occurred, where the change in deposition was caused by the supply of larger land sediments that caused the deposition of the Ombilin Formation to be deposited in the marine environment of the Transition-Nerritic Edge based on the bathymetry results. The research results are expected to enable geological information to gain in-depth knowledge and experience about the history of deposition and assist in geological modeling.